Learning Route: Learning from climate change adaptation innovative experiences of communities and local governments in ASALs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The Learning Route, “Learning from climate change adaptation innovative experiences of communities and local governments in ASALs”, aimed to faciliate learning by national decision makers in Kenya, Ethiopia, Tanzania and Uganda from community and local level experiences in ongoing climate change adaptation planning and action in arid and semi-arid lands in Kenya.